The Concept of Bâ’ah in Hadiths of Islamic Family Law and its Relevance in Marriage Age - Ismail Pane; Syamruddin Nasution; Khairunnas Jamal; Amru Hasibuan; Wira Lestari; Fatahillah bin Muhammad Syahrul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aims to examine the concept of al-Bâ’ah in the hadits of Prophet Muhammad (peace be upon him) and to analyze its relevance to the determination of marriage age within contemporary society. The concept of al-Bâ’ah is a term frequently used in hadiths concerning Islamic family law, particularly those related to the recommendation of marriage for individuals who possess the necessary capability. However, the understanding of this concept is not limited merely to biological capability; it also encompasses economic, psychological, social, and spiritual aspects that serve as prerequisites for establishing a family characterized by sakinah (tranquility), mawaddah (affection), and rahmah (compassion). This research employs a library research method with a qualitative approach and thematic hadith analysis. The primary data sources consist of hadiths containing the term al-Bâ’ah along with their commentaries (syarḥ), while the secondary data sources are derived from Islamic jurisprudence (fiqh) literature, Islamic family law references, and regulations concerning the legal age of marriage. Data analysis is conducted through the inventory and collection of relevant hadiths, critical examination of their interpretations, contextual analysis, and the assessment of their relevance to modern social realities. The findings reveal that al-Bâ’ah in the hadith literature carries a comprehensive meaning, encompassing physical capability to fulfill reproductive functions, financial capability to provide family maintenance, and mental and emotional readiness to bear the responsibilities of married life. Therefore, indicators of marital readiness in Islam are not determined solely by biological age but also by an individual’s level of maturity across various dimensions of life. In the contemporary context, the concept of al-Bâ’ah remains highly relevant to policies establishing a minimum legal age for marriage, as such policies aim to ensure the physical, psychological, and social maturity of prospective spouses.